PUBLIC ADMINISTRATION: MODERNIZING THE CURRENT MODEL OF STATE MANAGEMENT - E. V. Ohotskii (Vestnik MGIMO-Universiteta)
Applying the method of retrospective analysis the article deals with the process of forming the scientific fundamentals and the search by the international community of effective and adequate to the current stage of social development public administration system. The author attempts to analyze, in a number of cases in terms of models, features of public administration systems at different stages of historical development, drawing attention to reasons why the Soviet model of public administration did not manage to meet competition, did not provide the required social effect and as a natural result suffered a defeat in the global confrontation between the two social systems. Current models and theoretical concepts of public administration, especially the "new public administration", which became scientific basis for administrative reforms implemented in many countries, are the particular subject of scientific analysis. The author draws attention to major comprehensive characteristics of modern state public administration: making it impossible to absolutize principles of traditional hierarchy system of forced administration; globalization - gradual destruction of boundaries between national and international levels of administration, the growing role of supranational subjects of administration relations; informatization - increasing importance of information and communication technologies and of political networks: development of civil society, especially political parties and non-governmental organizations, growing public involvement in discussion and adoption of the most important administrative decisions; making the state policy more pluralistic and which will result in the formation of nonlinear - humanistic social consciousness as the intellectual basis of modern social governance. The author's position is that Russia is yet to solve the issue of choosing a public administration model that would be effective for further administrative modernization of the country. It seems that for our country any specific model of administration in its pure form, even the one considered to be the most popular in modern science and global practice, is unlikely to fit. Taking into consideration the logic, historical continuity, nonlinearity of modernization reforms and logical determinacy of social systems it looks like we are to integrate the best of the global public administration practice, especially those elements that will actually facilitate the rise of Russia as a modern democratic social law-governed state.